Methisoprinol as an immunomodulator for treating infectious mononucleosis - Maharani Laillyza Apriasari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Infectious mononucleosis (IM) is the self limiting disease that associated with primary Epstein Barr virus (EBV). It is a gamma herpes virus. EBV infection is follows saliva-transfer by kissing or sexual intercourse. The most clinical manifestation in IM consists mainly of the specific sign: pharyngitis, fever, and lymphadenopathy. The main therapy is supportive treatment. Actually the antiviral therapy is required for the host with high response immune. Purpose: The aimed of this study was to report the therapy of IM using methisoprinol. Case: The woman patient, 33 years old, came to hospital by suffering pharyngitis and swolen on left neck. It had been since 3 days ago. Case management: She had come to Puskesmas that were given amoxycillin capsul 500 mg three times a day for three days and paracetamol tablet 500mg three times a day for three days, but she was still ill. Then she came to RSGM Hasan Aman Banjarmasin. She was diagnosed as IM. The instruction were isolation and bed rest for a week. She had to eat sofly and drink water highly. The therapy were amoxycillin capsul 500 mg three times a day for seven days, methisoprinol caplet 500 mg three times a day for seven days, natrium dikofenak tablet 50 mg three times a day for seven days. She was asked to see the dentist next 7 days. In this case, she were not given acyclovir. Conclusion: IM is self limiting disease. IM is the disease with spesific clinical syndrome that associated with primary EBV infection. Depend on the base of clinical experiences, the supportive treatment is adviced for patient of IM. Methisoprinol has both immunomodulator and antiviral properties.